1985
DOI: 10.1002/dc.2840010411
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneur oblastoma: Cytologic features with differential diagnostic considerations

Abstract: A case of recurrent esthesioneuroblastoma was diagnosed by fine-needle aspiration of a midcervical mass. The cytologic features that characterize this uncommon neoplasm include uniform, small, round-to-oval cells with coarsely granular chromatin, multiple small nucleoli, prominent nuclear membranes, and scant cytoplasm. Morphologically and ultrastructurally, esthesioneuroblastoma cells resemble those of sympathetic neuroblastomas. Both tumors show rosette formation and minimal cellular pleomorphism, and, by el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…While some suggestion of nuclear molding within small cell groups was present in our air-dried smears, on alcohol-fixed, H&E-stained slides there was nuclear overlapping in the cell groups rather than nuclear molding. Fagan 8 found nuclear molding infrequently, while Jobst and Collins 1,5 described it as occurring more commonly.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While some suggestion of nuclear molding within small cell groups was present in our air-dried smears, on alcohol-fixed, H&E-stained slides there was nuclear overlapping in the cell groups rather than nuclear molding. Fagan 8 found nuclear molding infrequently, while Jobst and Collins 1,5 described it as occurring more commonly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports that describe the cytologic findings of ONB strongly support our diagnosis. 1,[3][4][5][6]8 In general, the cytologic features of ONB mimic those of conventional neuroblastoma. [9][10][11][12][13] Overall, authors found single cells and cell groups with a variable number of rosettes or pseudorosettes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations